Identification of nifD and nifH Genes of Methanotrophic Bacteria from Rice Field - Ari Fina Bintarti; Iman Rusmana; Aris Tri Wahyudi (ANNALES BOGORIENSES, 2014)
Metanotrophic bacteria have ability to oxidize methane and fix atmospheric nitrogen, hence the bacteria has an important role as a nitrogen source provider on wetland area like rice fields. Nitrogen fixation process is catalyzed by the nitrogenase enzyme complex, encoded by nifD and nifH genes. However, characteristic of these genes from indigenous-methanotrophic bacteria still poorly understood. Hence, nifD and nifH genes of methanotrophic bacteria isolated from rice fields in Indonesia (BGM3, BGM9, SS1, SS3, SS10, ST18, SP3 and INP4) were identified and characterized. Detection of nifH and nifD genes was conducted by polymerase chain reaction (PCR) amplification. nifH and nifD gene sequences were analyzed using BLAST-X and phylogenetic trees were constructed using Neighbour Joining method. Based on nifH sequences analysis, SS1 closely related to Beijerinckia mobilis and SS3, SS10, ST 18 closely related to Beijerinckia indica subsp. indica ATCC 9039, while, BGM3, INP4, and BGM9 related to nifH of uncultured nitrogen-fixing bacterium. In other hand, sequence analysis of nifD gene showed that SS1, SS3, SS10, ST 18 closely related to B. indica subsp. indica ATCC 9039 and BGM3, BGM9, INP4 closely related to Xanthobacter autotrophicus Py2. Identification by 16 SrRNA indicated that SS1, SS3, SS10, and ST18 had closeness to Beijerinckia sp. P310-1, while INP4 closely related to Xanthobacter sp. M5C24.